Comparative study of celluloses from biofilm-forming bacteria for development of cellulose-reinforced Product - Zakaria, Mohd Nazarudin; Raja Yahya, Mohd Fakharulzaman; Abd Rahman, Sukirah; Kamaruddin, Nooramirah; Othman, Maizatulnisa; Bahari, Shahril Anuar (Blue Eyes Intelligence Engineering & Sciences Publication Pvt. Ltd., 2015)
This study was conducted to compare the celluloses from Acetobacter xylinum and Pseudomonas fluorescens. Results showed that A. xylinum and P. fluorescens produce insoluble and soluble cellulose respectively. The agitation at several speeds was found to affect the form and yield of bacterial celluloses.Based on FTIR spectroscopy,the biochemical composition of A. xylinum cellulose was apparently distinct from that of p. fluorescens with regards to the spectral region between 830 cm-1 and 1400 cm-1.Sample preparation of P. fluorescens cellulose for XRD analysis was unsuccessful due to its high solubility in culture medium whilst XRD analysis demonstrated the high crystallinity (92.13%)of A.xylinum cellulose. Collectively, the variations between A.xylinum and P. fluorescents celluloses could be observed in terms of cellulose form, cellulose yield, biochemical composition and crystallinity. The findings from this study are expected to assist the industries in choosing the right source of bacterial cellulose for their commercial products.